PENGARUH METODE PEMBELAJARAN ROLE PLAY DAN STORY TELLING BERBANTUAN VIDEO TERHADAP KETERAMPILAN BERBICARA BAHASA INGGRIS DITINJAU DARI MOTIVASI BELAJAR (Studi Eksperimen Pada Siswa Kelas 8 di SMP Kecamatan Kota Kudus, Jawa Tengah Tahun Pelajaran 2013/ - EQI ASTUTI, ANA (Jurnal Teknologi Pendidikan dan Pembelajaran, 2014)
Background:English is very important to develop the human resources.  Speaking skill is the most important skill of the four language skills which has to be improved.This research is intended to find out whether there is difference of speaking skill achievement between the students taught by Role Play and those by Story Telling and there is influence difference between the students who have high motivation and those who have low motivation. Method: This experimental study was carried out at SMP 2 Kudus and SMP 1 Kudus. The population of this research is the students of the eighth grade in Kecamatan Kota in Kudus, Central Java in academic year 2013/2014. This research used cluster random sampling in taking the sample. The two instruments were tried out to get validity and reability for the quetionnaire and readability percentage for speaking test. Then the data was analyzed by using multifactorial analysis of variance ANOVA 2x2 and Tukey test. Before conducting the ANOVA test, normality and homogeneity test were conducted.Result: After the data were analyzed, the findings are as follow:  (1) There is difference of speaking skill achievement between the students taught by Role Play and those by Story Telling, Fvalue = 51,512 > Ftabel 4,027. The students who taught by using Role Play have better achievement. (2)  There is influence difference between the students who have high motivation and those who have low motivation, Fvalue = 5,345 > Ftabel = 4,027. The students with high motivation have better achievement. (3) There is influence interaction between Role Play and Story Telling related to motivation, Fvalue = 7,952 > Ftabel = 4.027. Keyword: Role Play, Story Telling, Motivation, Speaking Skill.